Improving Patient Safety and Hospital Service Quality Through Electronic Medical Record: A Systematic Review - Firdaus, Muhammad (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
To understand the Electronic medical records (EMR) role in improving patient safety and hospital’s service quality. Articles that included and assessed for the eligibility in this review was an article that show an effect of patient’ safety, and product quality in hospital in correlation on using EMR. The most important function of EMR implementation is to improve patient safety in hospital, in addition to reducing cost. EMR reduce excess cost of Hospital Acquired Condition (HAC) by 16%, reduce death due to HAC by 34%. Doctor and nurse’s belief that the quality of patient data is better when EMR are easier to use and suit with their dialy routine. EMR can improve patient safety, but its use require some skills in technology so it won’t turn to harm patients’ safety. The implementation EMR requires the ability of skilled human resources in using technologies, computer and programs